The Impact of Brand Image & Brand Trust on Consumer Purchase Intention Brand Study BYD Electrical Vehicle in JABODETABEK, Indonesia - Febrian Adhitya Nugraha; Nurliya Apriyana (Golden Ratio of Marketing and Applied Psychology of Business, 2027)
Rising urban air pollution driven largely by transportation emissions has intensified the urgency of accelerating electric vehicle adoption in Indonesia, yet public interest and understanding of EVs remain strikingly low despite BYD's rapid sales growth. This gap underscores the need to examine the psychological and perceptual factors that drive consumer purchase intention toward BYD. This study aims to examine the influence of brand image and brand trust on the purchase intention of BYD electric vehicle consumers in the Greater Jakarta (Jabodetabek) area. A quantitative research approach was employed using a purposive sampling technique, involving 154 respondents. Data were collected through a four-point Likert-scale questionnaire and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression with SPSS. The results indicate that both brand image (t = 4.783; p = 0.001) and brand trust (t = 5.123; p = 0.001) have a positive and statistically significant effect on purchase intention. These findings suggest that strengthening brand image and enhancing consumer trust are critical factors in increasing consumers' purchase intention toward BYD electric vehicles in Indonesia.